Effect of irrigation and land configuration on productivity of summer green manure crops and their incorporation on rice yield in Punjab - SINGH, C. B.; KAHLON, M. S.; DHINGRA, MADHU (Journal of Soil and Water Conservation, 2020)
Scarce water supplies and rising cost of fertilizers merit their judicious use in agriculture and thus greater emphasis towards green manures. In intensively-cropped Punjab state of India, alarming decline in groundwater resources necessitates improvement of water use and higher biomass productivity of green manure crops during summer. A field study was conducted to examine the combined effect of green manure crops, irrigation and land configuration on biomass yield and water productivity of summer green manure crops. This along with the effect of their incorporation on performance of rice crop during 2015 and 2016 at Punjab Agricultural University, Ludhiana, Punjab was observed. The treatments included three crops viz., cowpea, sunn hemp and sesbania in main plots and combination of two irrigation regimes (I1 and I2 based on net cumulative pan evaporation); two land configurations (flat-sowing, and bed-sowing in paired rows) in sub plots. After green manuring, rice crop was raised with two levels of N (60 and 120 kg ha-1) with and without green manure. Mean dry biomass yield at 8 weeks after sowing of sunn hemp was higher by 7 and 23 percent, respectively over sesbania and cowpea. More frequent I1 irrigation regime recorded 10.8 q ha-1 higher biomass over I2 (64.6 q ha-1) while utilizing 49 per cent more water. Flat sown crop registered higher biomass by 8.2 q ha-1 over bed furrow (65.9 q ha-1) that consumed 170 mm less water. Interaction of factors revealed that increase in biomass with flat was greater in I1 (9.7q ha-1) over I2 while corresponding value in bed- furrow was 6.8 q ha-1. Frequent irrigation reduced WP from 20.0 kg ha-1 mm-1 in I2 to 15.6 kg ha-1 mm-1 in I1 regimes. Bed-furrow construction enhanced WP by 34% over flat (15.2 kg ha-1 mm-1). Increase in WP with bed-furrow was more in I2 (5.8 kg ha-1 mm-1) than in I1 regime (4.6 kg ha-1 mm-1) over flat. Bed-furrow helped to achieve higher WP in sunn hemp than sesbania and cowpea. Rice yield was at par with incorporation of green manure with both N levels as well as 120 kg N ha-1 without green manure. However, 60 kg N ha-1 without green manure recorded significantly lower paddy yield. Green manure amendment improved soil physical properties by 0.25 mm mean weight diameter, 8.5% water stable aggregates, 0.33 cm hr-1 infiltration rate and 0.16% organic carbon.